Peningkatan kemampuan pemecahan masalah matematis siswa melalui model make a match berbantu media kenyang - Mega Ayu Putri Hapsari; Lovika Ardana Riswari; Denni Agung Santoso (Papanda Journal of Mathematics and Science Research, 2025)
The suboptimal application of learning models and media results in students having difficulty understanding questions, leading to low mathematical problem-solving skills. This study aims to determine the enhancement of students' mathematical problem-solving abilities through the implementation of the Make a Match model supported by KENYANG media (Kartu Menyenangkan). This research employs the Classroom Action Research (CAR) method, which takes place over two cycles, with two meetings in each cycle. The stages of this research follow the Kemmis and McTaggart model, consisting of planning, implementation, observation, and reflection. The data collection techniques used in this study are observation, interviews, tests, and documentation, and the data analysis in this research incorporates both quantitative and qualitative analysis techniques The research results using the Make a Match model with the KENYANG media on angle material showed an improvement, evidenced by an average score of 67.75 in cycle I, which is categorized as sufficient. In cycle II, it increased to 78.67, categorized as good. The percentage of classical completeness improved from 50% in cycle I to 80% in cycle II. Therefore, it can be concluded that the Make a Match model using KENYANG media can enhance the mathematical problem-solving skills of fifth-grade students at SD 3 Undaan Lor. This research provides benefits for improving students' mathematical problem-solving skills on the angle material in fifth grade